1997
DOI: 10.1088/0266-5611/13/4/010
|View full text |Cite
|
Sign up to set email alerts
|

On the inversion of the geodesic Radon transform on the hyperbolic plane

Abstract: A new inversion formula for the geodesic Radon transform on the hyperbolic plane is derived and numerically implemented. This problem arises from an integral geometry approach to the electric impedance tomography where inverting the geodesic Radon transform is one of the steps towards reconstructing the unknown conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…For example, it was shown that the Radon transform on co-planar circles whose centers are restricted to a bounded domain is invertible [1]. Radon transforms on other smooth curves have also been considered [2][3][4]. Recently, a series of papers have explored a circular-arc transform which arises when the signal is generated by first-order Compton scattering of X-rays [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that the Radon transform on co-planar circles whose centers are restricted to a bounded domain is invertible [1]. Radon transforms on other smooth curves have also been considered [2][3][4]. Recently, a series of papers have explored a circular-arc transform which arises when the signal is generated by first-order Compton scattering of X-rays [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Here the geodesic Radon transform integrates along geodesics in H 2 with respect to the measure induced by the Riemannian metric on H 2 . Methods of harmonic analysis (Fourier and Radon transforms and their inversions) on the hyperbolic plane are well developed (e.g., [16,66,67,87,89,92]). One hopes to use them to invert the geodesic Radon transform, to de-convolve, and as the result recover β.…”
Section: Reconstruction Algorithms and The Hyperbolic Integral Geometrymentioning
confidence: 99%
“…In particular, the papers mentioned above contain explicit inversion formulas for the hyperbolic geodesic Radon transform. The formula obtained in [92] was numerically implemented in [48] and works as nicely and stably as the standard inversions of the regular Radon transform 8 .…”
Section: Reconstruction Algorithms and The Hyperbolic Integral Geometrymentioning
confidence: 99%
“…The difficulty of numerically implementing (4.11) lies in the fact that it is complicated to numerically implement a twodimensional non-Euclidean convolution on the hyperbolic space. In [26], Lissianoi and Ponomarev focus on the problem of numerically inverting the geodesic Radon transform by developing an algorithm, and the problem regarding the deconvolution is also considered there. For this purpose, they consider the inversion formula (4.6) and use it to derive an inversion formula for the geodesic Radon transform that it is more suitable for computations.…”
Section: ∂(∂U)mentioning
confidence: 99%